(untitled) (Actualizaciones en Sida e Infectología, 2022)
Disseminated histoplasmosis is a frequent opportunistic infection in HIV/AIDS patients. Cutaneous manifestations are common, the most frequent are molluscum contagiosum-like lesions, varicelliform eruption and papulo-necrotic lesions. We present a case of an atypical disseminated cutaneous histoplasmosis with pyoderma gangrenosum-like ulcers, diagnosed by direct examination of tissue smear. It is important to have a high clinical suspicion of this atypical presentation and to emphasize the usefulness of skin smear as a simple and effective test to establish its diagnosis.